Perceived Benefit of Immunization-Trained Technicians in the Pharmacy Workflow - Taylor G. Bertsch; Kimberly C. McKeirnan (MDPI AG, 2020)
Clinical community pharmacists have continually restructured their workflow to serve the community by optimizing patient care outcomes. Defining the perceived benefits of having an immunizing pharmacy technician in the workflow can help to redefine the way community pharmacists operate during patient immunization. The purpose of this study is to share the opinions of supervising pharmacists that have an immunizing technician within their workflow model and highlight their contributions. Pharmacists involved in this novel workflow model were interviewed two times, once in 2017 and then in 2020, to gauge opinions over time. Findings in the results of this study included such themes as: (1) Pharmacists' perceived improvement in workflow flexibility; (2) The choice of the correct technician to immunize within the pharmacy; (3) Pharmacists' perceived improved workflow time prioritization; (4) Limited available training as a barrier to implementation; and (5) The initial apprehension and later acceptance of pharmacists with respect to the innovation. As technician immunization administration spreads beyond early adopter states, further research into the impact on pharmacy workflow is needed.